2018
DOI: 10.1108/ijshe-10-2017-0175
|View full text |Cite
|
Sign up to set email alerts
|

University halls plastics recycling: a blended intervention study

Abstract: Purpose The problem of plastic wastes is serious nowadays worldwide, although plastic wastes recycling is already in practice. To promote sustainability in plastic waste recycling, the quality of wastes collected should be maintained well, resulted from a good recycling practice. This paper aims to study a new plastic recycling bin (PRB) and poster interventions on the enhancement of university hall residential students’ proenvironmental knowledge, attitudes and intended behaviours (KAB) and actual recycling b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…Convenience was also a persistent theme, with a suggestion that it was, at times, more convenient to behave unsustainably, 'some things we do recycle and some things we don't, and it basically depends on what is easier to clean' (Participant D). This led into themes surrounding facilities and public provision of bins confirming research by Zhang et al (2011) regarding convenience as a key motivation (see also Wu et al, 2013;Perrault and Clark, 2017b;Cheung, 2018).…”
Section: Limited By Perceived Lack Of Ability To Behave Sustainablymentioning
confidence: 88%
See 2 more Smart Citations
“…Convenience was also a persistent theme, with a suggestion that it was, at times, more convenient to behave unsustainably, 'some things we do recycle and some things we don't, and it basically depends on what is easier to clean' (Participant D). This led into themes surrounding facilities and public provision of bins confirming research by Zhang et al (2011) regarding convenience as a key motivation (see also Wu et al, 2013;Perrault and Clark, 2017b;Cheung, 2018).…”
Section: Limited By Perceived Lack Of Ability To Behave Sustainablymentioning
confidence: 88%
“…The influence of housemates and peers represents a significant influence on student behaviour (Chaplin et al, 2014;Meyer, 2015;Saladié and Santos-Lacueva, 2016;Watson et al, 2015;Başev, 2016;Hay et al, 2019). This is likely to result from social approval or disapproval (Chaplin et al, 2014;Meyer, 2015), suggesting a portion of individuals are recycling, not because of their own pro-environmental stance, but because of the concern for social acceptance and the impact of peer pressure (Chan and Bishop, 2013;Cheung, 2018;Zhang et al, 2017) This is supported by SUEZ's (2020) research reporting that 10% of students, describing themselves as non-committed recyclers, were motivated to recycle by 'nagging'. Consequently, recycling behaviour is not solely reliant on individual attitudes nor those of peers but represents a complex interplay between the two and may affect self-reported behaviours rather than observed ones (Cheung et al, 1999).…”
Section: Influence Of Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-formal education, as well as informal learning experience, has been increasingly emphasized for its importance in nurturing students’ competency in and positive attitude toward sustainability within higher education ( Tang et al, 2017 ; Gramatakos and Lavau, 2019 ). Various co-curricular approaches, such as campus organic learning gardens ( Duram and Williams, 2015 ; Luetz and Beaumont, 2019 ; Pérez-López et al, 2020 ), campus-based ecotourism ( Robbins et al, 2019 ), the co-planning of a roof-top garden and wastewater treatment facility by students and university colleagues ( Mateus et al, 2020 ), a marine conservation program ( Cheang et al, 2017 ) and a waste recycling program in campus halls of residence ( Cheung et al, 2018 ), have been found to motivate pro-sustainability behavioral and attitudinal changes amongst undergraduates.…”
Section: Introductionmentioning
confidence: 99%
“…To date, whilst there is certainly an extensive body of literature on public attitudes towards plastic waste, most of the research has focused on attitudes towards specific actions. For example, there have been focused considerations of topics such as: the outcomes of trialling a new recycling initiative in a university setting (Cheung et al, 2018); the factors influencing an individual's motivation to recycle including the role that the convenience of a recycling scheme and general environmental attitudes have on participation levels (Best and Kneip, 2011;Huffman et al, 2014;Saphores and Nixon, 2014); behaviour relating to the reuse/recycling of plastics (Babader et al, 2016;Khan et al, 2019) including what difference there is in the factors that motivate waste minimisation behaviour versus recycling behaviour (Barr et al, 2001;Tonglet et al, 2004); and factors leading to lifestyle changes such as a switch to using cloth bags from plastic bags (Ari and Yilmaz, 2017).…”
Section: Introductionmentioning
confidence: 99%